Rethinking Translation: Emergent, Geographic, and Transformative - Houston, Serin; Trudeau, Dan (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
The term “translation” shows up in myriad sites within and outside of academia. It is frequently used to explain processes of movement and connection between languages, places, contexts, and ideas. Despite this ubiquity, translation as a concept is undertheorized within social science academic discourse. This paper responds to this gap by epistemologically rethinking translation and arguing that translation is emergent and geographic. The practices, processes, and politics of translation, therefore, can generate conditions for social transformation, which can lead to co-liberation. With this in mind, we draw on ideas of “improvisation,” “accompaniment,” and “emergent strategy” to conceptualize our rethinking of translation. We illustrate the possibilities of our rethinking by tracing translation within and through the Race and Social Justice Initiative (RSJI) in Seattle, Washington, a municipal government-led endeavor to eliminate institutional racism and race-based disparities. Situating translation as emergent and geographic shifts attention to the ways and contexts through which possibilities for social change emerge in time and place. Thus, our theorizing of translation has broad utility for critical geographic inquiry and the specific study and praxis of local scale policy-making and governance.